2013
DOI: 10.1007/s00216-013-7200-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of moxifloxacin in urine using surface-enhanced Raman spectroscopy (SERS) and multivariate curve resolution on a nanostructured gold surface

Abstract: A simple procedure is proposed for the determination of the antibiotic moxifloxacin in urine using nanostructured gold as surface-enhanced Raman scattering signal enhancer. The standard addition method in conjunction to multivariate curve resolution-alternating least squares was applied to eliminate the matrix effect and to isolate the spectral contribution of the analyte. Even in the presence of unexpected interferences in the urinary media, it was possible to extract and quantify the analyte response, reachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Consequently, ways to overcome these issues should be sought. Urine and its constituents have been analyzed by SERS spectroscopy on more than one occasion [32,33]. The information about the components of interest was retrieved by applying mathematical procedure -multivariate curve resolution-alternating least squares (MCR-ALS) algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, ways to overcome these issues should be sought. Urine and its constituents have been analyzed by SERS spectroscopy on more than one occasion [32,33]. The information about the components of interest was retrieved by applying mathematical procedure -multivariate curve resolution-alternating least squares (MCR-ALS) algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…Marqués 24) studied the acid-base behavior of adenine, adenosine 3,5-cyclic monophosphate and poly(adenylic) acid at 37°C by a spectrophotometric titration in acetonitrile-water mixtures. Nigam et al 25) used MCR-ALS and ultraviolet 26) adopted standard addition method in conjunction with MCR-ALS in order to eliminate the matrix effect and to isolate the spectral contribution of analyte. They used nanostructured gold as a surface-enhanced Raman scattering signal enhancer for kinetic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…5b shows typical chromatogram obtained after in-tube SPME of spiked urine sample (Urine 1), which appearance of new sharp peak of the drug is obvious in spiked urine sample. Mamian-Lopez and Poppi reported that moxifloxacin is in the range of 700 to 1500 µg mL -1 in urine 22 . By our method these concentration can be easily detected.…”
Section: Analysis Of Urine Samplesmentioning
confidence: 99%